Outsourcing and insourcing in an international context - Schniederjans, Marc J. (M.E. Sharpe, 2005)
Designed for upper-level undergraduate or graduate courses in strategic management and other courses, this text focuses on concepts, processes, and methodologies for firms involved in outsourcing-insourcing decisions. It covers the international risk factors of this strategy, presenting a view of the positive and negative aspects of outsourcing.